Application of filtration blocking models to describe fouling and transmission of large plasmids DNA in sterile filtration - Salim, Affaro Affandy; Eli, Keshavarz-Moore; Henk, Versteeg (ELSEVIER, 2013)
Sterile filtration is considered as a final step in processing pharmaceutical grade plasmid DNA. During the development of the filtration process, fundamental understanding on the mechanism of fouling is critical to improve filtration operations. The mechanism of fouling of pQR150 (20 kb) and pGEc47 (56 kb) plasmids DNA during constant pressure filtration inside 0.22 µm PVDF membrane is experimentally investigated. The decline of filtrate flux as function of time is analysed using the framework of classical and combined blocking models. The results for both plasmids indicate a transition between fouling mechanisms. Initially, during the early part of the filtration, the intermediate blocking model provided the best fit of the experimental results suggesting that fouling of the membrane was mainly caused by deposition of particles onto its surface. Afterwards, the result trends were best captured by the standard blocking model indicating that internal fouling of the membrane was the dominant fouling mechanism. A study of the transmission of both plasmids shows a significant reduction of plasmid transmission which coincides with the transition of the fouling mechanism from intermediate to standard blocking. The study highlights how the fouling behaviour of large plasmid DNA during sterile filtration is determined by the complex interplay between the flexibility of the molecules and the internal structure of the membrane.